Outpatient parenteral antibiotic therapy for the treatment of prosthetic knee and hip infections in Belgium, a cost minimization analysis. Issue 1 (2nd January 2022) - Debaenst, Niels; Seyler, Lucie; Putman, Koen; Van Den Borre, Ina; Vanlauwe, Johan
ABSTRACT: Objectives: Prosthetic joint infections (PJI) are treated with prolonged periods of intravenous (IV) antibiotics combined with one or more appropriate surgical procedures. In Belgium, patients receive their IV treatments as inpatients, whereas in other parts of the world similar IV antibiotics can be given as outpatient parenteral antibiotic therapy (OPAT), without jeopardising patient outcomes. The purpose of this paper was to analyse the financial feasibility of OPAT for PJI in Belgium. Methods: Patients with PJI treated with a two-stage revision between January 2013 and June 2016 were selected for analysis of in-hospital costs. An OPAT cost simulation was made for comparable lengths of stay, for the different antimicrobial regimens used. A cost minimization analysis comparing the non-OPAT costs and the OPAT cost simulation was performed, with a sensitivity analysis accounting for cost uncertainties. Results: Based on the financial data of 12 two-stage revisions and 4 different antibiotic regimens, the average simulated cost difference for OPAT was €2.402 surplus for the patient, €-25.950 for health care and €-23.548 in total. Conclusion: Projected cost savings for OPAT-treatment of PJI are substantial. However, OPAT within the current Belgian system was significantly more expensive for the patients. This can be attributed to the Belgian health insurance system; its current reimbursement regulations prevent OPAT from truly making a breakthrough in Belgium.